Isolation of Conventional Murine Lung Dendritic Cell Subsets. (21st February 2018) - Bosteels, Cédric; Lambrecht, Bart N.; Hammad, Hamida
Abstract: The lungs are continuously exposed to environmental threats, requiring an adequate and stringent immune response of a heterogeneous set of effector cells. Dendritic cells (DCs) form a dense network in the respiratory mucosa and act as the central regulators of the different components of this response, both sensing the nature of the threats and precisely coordinating the effector mechanisms best suited for overcoming it. The DCs are classically subdivided in two main groups, plasmacytoid DCs (pDCs) and conventional DCs (cDCs), the latter being further subdivided into cDC1s and cDC2s based on ontogeny and their distinct non‐redundant functions. This protocol provides different enrichment methods and represents an up‐to‐date, universal framework that uses a minimal set of highly specific lineage markers to discriminate and sort pure cDC subsets from the murine lung but also across tissues and species which is an added value in intra‐ and interspecies comparative research. © 2018 by John Wiley & Sons, Inc.